2001
DOI: 10.1073/pnas.98.4.1889
|View full text |Cite
|
Sign up to set email alerts
|

A zinc finger-containing papain-like protease couples subgenomic mRNA synthesis to genome translation in a positive-stranded RNA virus

Abstract: The genome expression of positive-stranded RNA viruses starts with translation rather than transcription. For some viruses, the genome is the only viral mRNA and expression is regulated primarily at the translational level and by limited proteolysis of polyproteins. Other virus groups also generate subgenomic mRNAs later in the reproductive cycle. For nidoviruses, subgenomic mRNA synthesis (transcription) is discontinuous and yields a 5′ and 3′ coterminal nested set of mRNAs. Nidovirus transcription is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 49 publications
4
83
1
Order By: Relevance
“…Although the function of the N-terminal region of pp1a/pp1ab is not known, both the transcription-negative phenotype of an alphavirus X domain mutant (31) and the conservation of a transcription factor-like zinc finger in coronavirus PLpros (32) indicated that p195/p210 might be involved in coronavirus RNA synthesis. This hypothesis is strongly supported by a recent report in which the equine arteritis virus nonstructural protein 1, which, most probably, is a distant homolog of the coronavirus PLpros, is shown to be a transcriptional factor that is indispensable for sg mRNA synthesis (33).…”
supporting
confidence: 65%
“…Although the function of the N-terminal region of pp1a/pp1ab is not known, both the transcription-negative phenotype of an alphavirus X domain mutant (31) and the conservation of a transcription factor-like zinc finger in coronavirus PLpros (32) indicated that p195/p210 might be involved in coronavirus RNA synthesis. This hypothesis is strongly supported by a recent report in which the equine arteritis virus nonstructural protein 1, which, most probably, is a distant homolog of the coronavirus PLpros, is shown to be a transcriptional factor that is indispensable for sg mRNA synthesis (33).…”
supporting
confidence: 65%
“…Accessory proteases fall predominantly within the papain family, are found mostly in the N-terminal region of positive-stranded RNA virus polyproteins, and are wide spread among positive-stranded RNA viruses. Although not directly involved in genome replication, accessory proteases appear to be indispensable for virus reproduction (20,32,33). Remarkably, functional HCV subgenomic RNAs replicate in the absence of the structural proteins and NS2 in cell culture and suggest that the NS2/3 protease activity is not essential for RNA replication (34).…”
Section: Discussionmentioning
confidence: 99%
“…These two precursor proteins are extensively processed after translation into at least 13 nsps (nsp1-12, including nsp7 a/b; Figs. 4 and 5, Table 1) by three viral proteases (nsp1, nsp2, and nsp4) (Barrette-Ng et al, 2002;den Boon et al, 1995;Snijder et al, 1995a;Snijder and Meulenberg, 1998;Snijder et al, 1994Snijder et al, , 1995bSnijder et al, , 2001Tijms et al, 2001;van Aken et al, 2006a,b,c;van den Born et al, 2007;van Dinten et al, 1996van Dinten et al, , 1999Wassenaar et al, 1997;Ziebuhr et al, 2000). The greatest variation in the EAV replicase gene occurs in the portion of ORF1a encoding the nsp2 protein, with considerable variation at amino acids 388-488 (Balasuriya et al, 2004b;Miszczak et al, 2012;Zhang et al, 2008a,b,c).…”
Section: Genome Organizationmentioning
confidence: 99%
“…However, PCPa may possess RNA-binding and/or protein-binding activities (along with PCPb), serving as a platform for the ZF during transcription. Therefore, the structural integrity of nsp1 is essential since all three domains are required for trans-activation of sg RNA synthesis (Tijms et al, 2001). It has been reported that nsp1 is essential for sg RNA transcription but dispensable for genome replication (Tijms et al, 2007).…”
Section: Nonstructural Proteins Of Eavmentioning
confidence: 99%
See 1 more Smart Citation